2020
DOI: 10.1111/fcp.12549
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MDR‐1 gene expression, BAX/BCL2, caspase‐3, and Ki‐67 by nanoencapsulated imatinib and hesperidin to enhance anticancer activity and ameliorate cardiotoxicity

Abstract: There is a great demand to introduce new approaches into cancer treatment field due to incidence of increased breast cancer all over the world. The current study was designed to evaluate the role of imatinib mesylate (IM) and/or hesperidin (HES) nanoparticles alone or in combination in enhancing the anticancer activity and to investigate the ability of nanoencapsulation to reduce cardiotoxicity of IM in solid Ehrlich carcinoma (SEC)‐bearing mice. IM and HES were loaded into PLGA (poly(lactic‐co‐glycolic acid) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…28 El Sisi et al reported that imatinib could increase the expression of Bax and decrease the expression of Bcl-2 by targeting Bax/Bcl-2, thus enhancing its antitumor activity. 29 In this study, it was demonstrated that the mRNA expression of PTEN in A549 cells and A549/DDP cells decreased. Moreover, Western blot assay showed that miR-29b-3p Mimics could up-regulate the protein expression of apoptosis-related gene Bax and tumor suppressor gene PTEN, and down-regulate the protein expression of Bcl-2 and COL1A1.…”
Section: Discussionmentioning
confidence: 61%
“…28 El Sisi et al reported that imatinib could increase the expression of Bax and decrease the expression of Bcl-2 by targeting Bax/Bcl-2, thus enhancing its antitumor activity. 29 In this study, it was demonstrated that the mRNA expression of PTEN in A549 cells and A549/DDP cells decreased. Moreover, Western blot assay showed that miR-29b-3p Mimics could up-regulate the protein expression of apoptosis-related gene Bax and tumor suppressor gene PTEN, and down-regulate the protein expression of Bcl-2 and COL1A1.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, El‐Sisi et al (2020) evaluated the in vivo anti-cancer efficacy and toxicity of poly (lactide-co-glycolide) (PLGA)-encapsulated imatinib mesylate and/or hesperidin in Swiss albino mice bearing solid Ehrlich carcinoma (SEC). The study showed that the intraperitoneal injection of nano-encapsulated imatinib mesylate (Nano-IM; 3.75 or 6.25 mg/mL) or nano-encapsulated hesperidin (Nano-HES; 6.25 mg/mL) induced a more significant reduction in both tumour volume and tumour weight than their respective treatment (50 mg/kg).…”
Section: Strategies To Enhance Bioavailability Of Hesperidin and Hesperetinmentioning
confidence: 99%
“…It has also been evaluated to work in combination with cisplatin to treat non-small-cell lung cancer (NSCLC) patients in clinical trials, as ginseng is able to enhance the cytotoxicity of multiple chemotherapy drugs [ 26 ]. Regarding breast cancer, hesperidin was shown to increase the cytotoxicity of tamoxifen, a selective estrogen receptor modulator, and imatinib mesylate, a platelet-derived growth factor (PDGF) receptor inhibitor, when treating breast cancer cells [ 27 , 28 ]. In addition, combination with hesperidin could potentially prevent the resistance of MCF-7 to doxorubicin treatment in breast cancers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%